Cervical Dysplasia : Diagnosis, Treatment and Evolution - Zambrano Burga, Aníbal V. (1971)
We studied 150 women with cervical dysplasia . Age , sexual activity and parity : the existence of the following factors as determinants of dysplastic lesion was found . Dysplasias have no symptomatology . The presenting symptoms are varied, depending on multiple factors or associated injuries. Dysplasia occurs in the earliest age carcinoma in situ and invasive cancer it . The vaginal cytology in the study of patients with dysplasia is crucial . Cytological changes were often the first evidence that guided diagnosis and subsequent detection of lesion progression to more severe dysplasia and carcinoma in situ even degree . Biopsy of cervix is ​​a very useful method in the diagnosis of dysplasia should be combined with conization in select cases. Trichomonas vaginalis has been commonly found in patients with dysplasia. Conization and hysterectomy are the methods gave better results in the treatment of dysplasia . In its evolution dysplasia can be: reversible or at least not detectable , persistent or become more severe. In dysplastic patients where the natural history of the lesion by conization or hysterectomy electrocoagulation substantial proportion did not change , it was possible to detect , after the diagnosis of dysplasia , carcinoma in situ . The following evidence suggests that dysplasia is a precursor to cervical carcinoma were found : a) Existence of common factors present in both dysplasia and carcinoma (age , parity , sexual activity). b ) Relative prevalence of the three lesions in successive five-year periods , is coincident with the change of dysplasia to invasive carcinoma. c ) Demonstration in women with dysplasia, controlled by months , of the existence of in situ carcinoma. d ) Find areas of dysplasia lesions adjacent to carcinoma in situ.